Leakage current characteristics and ageing assessment technology of roof arrester under ultra harmonics overvoltage. (27th August 2021) - Sun, Jixing; Ding, Fan; Lv, Yunlong; Ren, Jiayi; Song, Sibo; Li, Tiance; Zhi, Qingyun; Guo, Changwang
Abstract: The large leakage current of the roof arrester caused by the high‐frequency resonant overvoltage on the high‐speed train occurs intermittently, which will cause the arrester to overheat locally. In this work, the overheating issue of the arrester under Ultra Harmonics Overvoltage is studied. Then, the relationship between the active power and the voltage (including amplitude and frequency) of the arrester is investigated, and the impact mechanism of the harmonic voltage on the overheating fault of the arrester is analysed based on experiments in this work. It is found that the total leakage current of the arrester is proportional to the amplitude and frequency of the applied voltage. The internal resistance of the arrester is independent of the amplitude of the voltage, but it will decrease with the increase of the frequency. The main reason that leads to thermal breakdown of the arrester valve under high‐frequency harmonic voltage is the heating power elevation of the arrester valve. The research study can provide theoretical basis and data support for the design, type selection and monitoring of the high‐speed train roof arrester.